2016
DOI: 10.1038/538311a
|View full text |Cite
|
Sign up to set email alerts
|

There is a blind spot in AI research

Abstract: Chicago police use algorithmic systems to predict which people are most likely to be involved in a shooting, but they have proved largely ineffective. COMMENT © 2 0 1 6 M a c m i l l a n P u b l i s h e r s L i m i t e d , p a r t o f S p r i n g e r N a t u r e . A l l r i g h t s r e s e r v e d .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(171 citation statements)
references
References 3 publications
2
161
0
8
Order By: Relevance
“…Finally, a social-systems analysis is currently missing from research on conversational agents, an absence that has also been reported for artificial intelligence applications in previous literature 59 . There are currently no agreed methods to assess the long-term effects of this technology on human populations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a social-systems analysis is currently missing from research on conversational agents, an absence that has also been reported for artificial intelligence applications in previous literature 59 . There are currently no agreed methods to assess the long-term effects of this technology on human populations.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying Max's inference was his assumption that people with bad credit scores do not earn such salaries. Director of data science Martin and DeepNetwork's CTO Justin 19 , however, believed otherwise. Arguing that the relationship between credit score and salary was tenuous at best, they told Max that his interpretation was incorrect.…”
Section: Max (Data Scientist)mentioning
confidence: 99%
“…Fears that AI might jeopardize jobs for human workers 7 , be misused by malevolent actors 8 , elude accountability or inadvertently disseminate bias and thereby undermine fairness 9 have been at the forefront of the recent scientific literature and media coverage. Several studies have discussed the topic of ethical AI [10][11][12][13] , notably in metaassessments [14][15][16] or in relation to systemic risks 17,18 and unintended negative consequences like algorithmic bias or discrimination [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%